2018
DOI: 10.1177/1052562918812154
|View full text |Cite
|
Sign up to set email alerts
|

Invisible or Clichéd: How Are Women Represented in Business Cases?

Abstract: Women represent just under 50% of undergraduate business graduates and 36% of MBA graduates. Despite their strong presence in management education programs, women are noticeably absent from business case studies-a key pedagogical tool for instruction within management education programs worldwide. While case studies inform students about business processes, decision making, strategy, and leadership and management challenges, they also promote unintentional learning about gender. We argue that case studies cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 75 publications
1
14
0
Order By: Relevance
“…The authors found other stereotypes reinforced in cases related to race, national origin and age as well. Similar findings were identified in study by Sharen & McGowan (2018), which found that 20% of business school case studies among their sample had female protagonists and those females were represented as emotional, cautious, overwhelmed and less visionary, action-oriented, and innovative than men. In addition, female protagonists' credentials were mentioned more frequently as opposed to their male colleagues.…”
Section: Perpetuation Of Stereotypessupporting
confidence: 85%
“…The authors found other stereotypes reinforced in cases related to race, national origin and age as well. Similar findings were identified in study by Sharen & McGowan (2018), which found that 20% of business school case studies among their sample had female protagonists and those females were represented as emotional, cautious, overwhelmed and less visionary, action-oriented, and innovative than men. In addition, female protagonists' credentials were mentioned more frequently as opposed to their male colleagues.…”
Section: Perpetuation Of Stereotypessupporting
confidence: 85%
“…By doing a reveal in real time and asking students to reflect on how their perceptions shape the language they use and the world they construct, we nudge our students toward more inclusive action. We can also follow the lead of Sharen and McGowan (2019) who argue for providing positive female role models in the written cases we ask our students to read—and, we would add, in the guest speakers we ask them to see in our auditoriums and lecture halls—because “as educators, we consciously and unconsciously shape our students’ identities as managers and leaders through what we teach, how we teach it, our choices as role models, the discussions we entertain in the classroom, and the materials we select” (p. 159).…”
Section: Discussionmentioning
confidence: 99%
“…Business schools primarily assume and teach from cisgender and heteronormative perspectives throughout the curriculum and delivery of the program . The assignment of gender roles based on traditional gender expectations and norms is pervasive in business education, ranging from vernacular (chairman, businessman); representation (the overwhelming focus on male protagonists in business cases, to the near exclusion of women or complete exclusion of nongender conforming individuals in business education materials); or stereotypes (males as business leaders, females as support personnel; Sharen & McGowan, 2019, Symons & Ibarra, 2014. Critiques of this persistent imbalance are fueling change within the field, but the focus has largely been on greater representation of females rather than on the inclusion of gender nonconforming individuals.…”
Section: Gender and Business Educationmentioning
confidence: 99%
“…This study confirms a gap in the existing literature that would aid business educators in the development of curriculum, the identification and development of teaching/learning resources, and the training of faculty in the delivery and implementation of gender inclusive concepts and materials. Much of the existing business education materials lack equal or balanced representation of heterosexual cisgender women (Sharen & McGowan, 2019;Symons & Ibarra, 2014), and according to the articles found in this study, representation of nonheteronormative individuals and perspectives is limited (Sanchez, 2019). Two options for inclusion of gender nonconforming individuals are (a) to start including more gender nonconforming individuals and perspectives (including language) in business education materials such as textbooks, cases, readings, and so on (Harris et al, 2017) and (b) to explicitly include gender nonconforming topics in the content of business education courses .…”
Section: Development Of Curriculum Finding/developing Resources and Training Facultymentioning
confidence: 99%